The Effect of Auxiliary Tools in Developing Locomotors Cohesion and Learning the Spike Skill of Volleyball for Students - Abdallah Sekiy, Rouaa; Abd Zaid Aldulaimy, Nahida (International Journal of Psychosocial Rehabilitation, 2020)
The use of aids is a basis for progress in the level of performance by arriving at the most accurate knowledge in the performance of any skill in volleyball. As for the research problem, it may not use appropriate aids for the abilities and capabilities of the learners, which leads to their feeling of boredom and lack of effective participation in the special exercises for skills. The aim of the research is to design a motor link test and a technical performance test for the spike-hitting skill of volleyball for students. The two researchers followed the experimental approach in designing the two equivalent groups for the research sample of (30) students from the second stage students in the College of Physical Education and Sports Sciences at the University of Kufa for the academic year (2018-2019). A sample of the second stage students numbered (15) students, and after conducting the pre-test, the experimental group followed the units by auxiliary means, within a period of (10) weeks with two educational units per week, and thus the number of the total units reached (20) units per unit time of learning (90) minutes. the researcher interfered with the priest The main educational unit was his time (60 minutes), and after the completion of the implementation of vocabulary, tests were conducted on the two sets of meta-search control and experimental. The two researchers reached the conclusions by designing tests for kinematic correlation and testing the technical performance of the spike-hitting skill of volleyball for students, and the two researchers recommended emphasizing the introduction of new aids in educational units to develop the technical performance of the spike-hitting skill of volleyball for students.